Еstimation of the beam power gain for deep-subcritical uranium assembly Quinta under relativistic proton, deuteron and carbon nuclei irradiation - Voronko, V.А.; Zhadan, А.А.; Sotnikov, V.V.; Adam, I.; Baldin, А.А.; Berlev, A.I.; Solnyshkin, A.А.; Tyutyunnikov, S.I.; Furman, W.I.; Husak, K.V; Zhuk, I.V (Вопросы атомной науки и техники, 2018)
The experimental study of the beam power gain for deep-subcritical uranium target assembly Quinta (mass of natural uranium 512 kg) under relativistic protons, deuterons and carbon nuclei irradiation is presented. The Quinta assembly was irradiated with 0.66 GeV protons, 1, 2, 4, and 8 GeV deuterons and 24, 48 GeV carbon nuclei from the Phasotron and Nuclotron accelerators at the Joint Institute for Nuclear Research (JINR), Dubna. The beam power gain values obtained for the target assembly Quinta were extrapolated for a quasi-infinite uranium target using the results of the R.G. Vasilkov et al. [1]. The obtained results can be used in the ADS reactor design.